IMMU-12. TUMOR CELL IDO ENHANCES IMMUNE SUPPRESSION AND DECREASES SURVIVAL INDEPENDENT OF TRYPTOPHAN METABOLISM IN GLIOBLASTOMA. (12th November 2021) - Zhai, Lijie; Bell, April; Ladomersky, Erik; Lauing, Kristen; Bollu, Lakshmi; Nuygen, Brenda; Genet, Matthew; Kim, Miri; Mi, Xinlei; Kocherginski, Masha; Wu, Jennifer; Schipma, Matthew; et al.
Abstract: OBJECTIVE: Indoleamine 2, 3-dioxygenase 1 (IDO; IDO1) is an immune checkpoint that's characterized as a potent immunosuppressive mediator through its ability to metabolize tryptophan and wild-type IDH patient-resected glioblastoma (GBM) expresses IDO in ≥ 95% of cases. Recent findings from our group led us to investigate the alternative hypothesis that IDO possesses immunosuppressive effects that are independent of its associated metabolic activity. METHODS: Murine GBM cell lines that overexpress either wild-type or enzyme-null IDO were created for in vivo characterization of IDO enzyme-independent immunosuppressive function. Microarray was conducted to identify human IDO expression-correlated genes, which were further investigated in human GBM cell lines, patient GBM tissues and plasma, as well as the TCGA database. Ex vivo cell co-culture assays and syngeneic mouse orthotopic GBM models were employed to study immunosuppressive mechanisms. RESULTS: Here, we demonstrate that non-enzymic IDO activity decreases survival in experimental animals and increases the expression of immunosuppressive complement factor H (CFH) in human GBM. CFH mRNA levels positively correlate with those of IDO and many other immunosuppressive genes in patient resected GBM and can be applied as a prognostic marker in both lower grade gliomas and GBM. Similar to IDO, the increased expression of CFH in patient-resected glioma was positively correlated with an increased signature for regulatory T cells (Tregs) and myeloid-derived suppressive cells (MDSCs). High expression of CFH in tumor cells increases intratumoral Tregs levels and decreases overall survival in mice with GBM, while inducing tumor associated macrophage cell differentiation. CONCLUSIONS: Here, we demonstrated that glioblastoma (GBM) cell IDO promotes the accumulation of intratumoral FoxP3 + regulatory T cells (Tregs) and tumor progression while decreasing overall survival - independent of IDO enzyme activity. Our study reveals a targetable non-metabolic IDO-dependent mechanism for future therapeutic intervention in patients with GBM.